"Opening" Art History: Exploring the Motivations and Practices of Faculty using Open Educational Resources in Lower-Level and General Education Art History Courses. Issue 1 (13th December 2021) - Chtena, Natascha
Although over the years the conceptual understanding of OER has improved, more insights are needed on faculty's discipline-specific practices with OER. This study explored the motivations and OER-related practices of faculty in lower-level and general education (GE) undergraduate art history courses in the United States. Using twelve in-depth interviews conducted over nineteen months, it investigated why, how and to what ends a diverse group of art historians use OER and related practices in their teaching. The study found six, discipline-specific main motivations for adopting OER, which extend well beyond cost savings for students. At the same time, only small changes were reported in faculty's teaching practices as a result of adopting OER. That is, OER didn't simply trigger pedagogical innovation by virtue of being adopted. Instead, these resources were strategically utilized by faculty to address existing teaching needs and goals, which were shaped by broader conversations and concerns within the field of art history. This suggests that it is impossible to disconnect OER from current pedagogic practices and models, as well as the social and disciplinary context in which they are employed.